FORMULATION DEVELOPMENT AND CHARACTERIZATION OF LAFUTIDINE RAFT SYSTEM - SAGAR, SHANTI; PRAMODINI, GAJJALA NARAHARI (International Journal of Pharmacy and Pharmaceutical Sciences, 2023)
Objective: The present research work is focused to develop in situ raft gel of lafutidine. Sodium alginate is one of the critical components for the development in situ raft system. Methods: The formulation was prepared using hydrophilic polymers such as ethyl cellulose, HPMC K4M, and chitosan. The formulations were subjected to evaluation characteristics such as pH, in vitro gelling time, viscosity, density, gel strength, drug-polymer compatibility studies, drug content floating lag time, swelling index, and in vitro release studies. Results: The pH of all the prepared batches was found in the range of 5.7 to 7.6. All the prepared formulations showed viscosity in the range of 264 to 320 cps, with gelling time from 4-7 s. For F1-F15 batches Floating lag time was found to be in the range of 9-24 sec. Densities of all formulations stomach specific in situ gels were in the range of 0.4 to 0.8 gm/cm3. The highest swelling index was observed in F15 with 14.16% Highest gel strength is exhibited by F15; all the formulations were in the range of 95.46–99.95, indicating the uniform distribution of the drug. Formulation F15 containing chitosan in combination with ethyl cellulose gave the highest drug release of 99.78% and also showed sustained and controlled release for up to 24h. Conclusion: F15 shows an R2 value of 0.999. As its value is nearer to the ‘1’ it is confirmed as it follows the Zero order release with an ‘n’ value is 1.5021 for the optimized formulation (F15) i.e., the n value indicates super case II transport and is considered as optimized formulation.